Pengaruh Pemberdayaan Wanita terhadap Pemilihan Penolong Persalinan pada Tenaga Kesehatan Terampil - Mirta Dwi Wulandari; Elfrida Zoraya (Media Kesehatan Masyarakat Indonesia, 2020)
The Maternal Mortality Ratio (MMR) in Indonesia has estimated 305 deaths per 100,000 live births in 2015. A large effort needed to reach SDG’s target of 70 maternal deaths in 2030, by increasing Skilled Birth Attendant (SBA) use. An increase in autonomy and women's empowerment were expected to be able to increase the role of women in decisions related to their health. This study examined the relationship of women’s empowerment with SBA use in Indonesia using the 2017 DHS. The number of samples in this study was 14,835 women aged 15-49 who had one or more children born, and were married or living together with their partners. Women’s empowerment indicators used in this study were educations, participation in decision-making, negotiating safer sex, and attitude towards wife-beating. Data analysis was performed using binary logistic regression analysis. Overall, women’s empowerment indicators except for participation in decision making significantly influenced SBA use even after controlled by sociodemographic characteristics. The results of this study indicated that the increased SBA use during childbirth can be done by increasing women's empowerment, including through education and delaying the age of marriage. Well-targeted policies can be carried out by identifying factors that increase SBA use.